Simulation of the impact of greening measures in an agricultural area of the southern Italy. (November 2015) - Cortignani, Raffaele; Dono, Gabriele
Highlights: Identification of farm types representative of the agricultural area of the southern Italy. Calibration of hybrid model by PMP methodology. Modelisation of CAP greening measures. Impact of the greening measures in terms of economic, social and environmental dimensions. Positive impact on curtailing the use of chemicals input and on crop diversity. Abstract: Together, sustainable management of natural resources and climate action form one of the three objectives of the 2014–2020 Common Agricultural Policy. This objective is being addressed by replacing the existing direct payments under Pillar 1 with a basic payment, combined with an additional payment conditional on farmers undertaking agricultural practices beneficial for the climate and the environment, a policy referred to as greening . In this study, the impact of greening was assessed using a hybrid model calibrated using positive mathematical programming. The model describes the macro-types of farm production in a Mediterranean agricultural area. The results show that greening was not beneficial throughout the study area and only some farm types have been particularly affected. However, greening appears to have a positive impact on curtailing the use of chemicals, particularly nitrogen, and on crop diversity.